ДОРИВОР ТИРНОҚГУЛ (CALENDULA OFFICINALIS L.)НИНГ ЎСИШ ВА РИВОЖЛАНИШ ХУСУСИЯТЛАРИ (Scientific journal of the Fergana State University, 2023)
Under the conditions of the NUUz Botanical Garden marigold  medicinal plants in the growth and development of phenological characteristics are studied.